2018
DOI: 10.3390/pharmacy6040132
|View full text |Cite
|
Sign up to set email alerts
|

Communications Skills in the Pharmacy Profession: A Cross Sectional Survey of UK Registered Pharmacists and Pharmacy Educators

Abstract: Objectives: To determine UK pharmacists’ experiences of their current communication skills and undergraduate training and to identify communication skills training and teaching at UK schools of pharmacy. Methods: Two surveys were developed. The first survey was sent to UK practicing pharmacists examining their current communication skills and interest in behavioural counselling techniques such as Motivational Interviewing (MI). A second survey was sent to all UK Schools of Pharmacy investigating communication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…On a scale where one was not prepared and five was fully prepared, the mean rating was 3 with over half of the participants developing their consultation skills after registration and the majority of pharmacists expressing a need for further training. A recent UK survey of 109 practicing community pharmacists by the authors of this paper [44] also showed that more than half of the participants in the survey who were taught consultation skills at an undergraduate level reported that they were not satisfied with their undergraduate training; ranking their consultation skills training as below 5 on a scale of 1 to 10 with 10 been very satisfied.…”
Section: Discussionmentioning
confidence: 82%
“…On a scale where one was not prepared and five was fully prepared, the mean rating was 3 with over half of the participants developing their consultation skills after registration and the majority of pharmacists expressing a need for further training. A recent UK survey of 109 practicing community pharmacists by the authors of this paper [44] also showed that more than half of the participants in the survey who were taught consultation skills at an undergraduate level reported that they were not satisfied with their undergraduate training; ranking their consultation skills training as below 5 on a scale of 1 to 10 with 10 been very satisfied.…”
Section: Discussionmentioning
confidence: 82%
“…This may explain why those qualified more recently report a much higher level of dedicated training in CSBC. A cross‐sectional survey of UK pharmacists ( n = 109) found similar results, with more than half reporting not receiving CSBC training as undergraduates or being dissatisfied with the training they had received, 44 whereas more recently qualified staff reported more training and greater satisfaction. These results suggest that pharmacy educators are also developing educational approaches to support development of CSBC and delivery of patient‐centred care.…”
Section: Discussionmentioning
confidence: 85%
“…Whilst the UK pharmacy curriculum includes relevant learning outcomes related to the demonstration of effective consultation skills and working with patients to decide a course of action [ 59 ], it is not at all clear that this means defining problems from the patient’s perspective (as true counselling would) or identifying personal goals (as motivational interviewing would). Whilst there is evidence to support the effectiveness of motivational interviewing for medicines management [ 60 ] and this has influenced modern undergraduate curricula; it remains unclear if these skills are widespread or utilised effectively without further professional development [ 61 , 62 ]. Many studies mentioned healthcare professional training but they did not describe the content and depth of this training [ 30 , 31 , 39 , 41 , 44 , 45 , 48 ].…”
Section: Discussionmentioning
confidence: 99%